2019
DOI: 10.1002/jctb.6205
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of an algae–fungi symbiotic system influence nutrient removal from synthetic wastewater

Abstract: BACKGROUND Algae–bacteria symbiotic system has attracted much attention in the fields of nutrients removal from wastewater. Fungi has also been demonstrated to promote the cultivation of microalgae. However, capability and mechanism of algae–fungi symbiotic system for nutrient removal remains unclear. RESULTS This study assessed the removal efficiencies of an algae–fungi symbiotic system of Chlorella variabilis NC64A and Ganoderma lucidum for chemical oxygen demand (CODcr), total nitrogen (TN), total phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The organic matter produced by algae through photosynthesis is utilized by fungi, while algae bene t from the winding and protection of fungal laments, absorbing various nutrients needed for growth from the environment (Jiang et al 2019). Studies have shown that in the process of symbiosis between microalgae and fungi, the sugar alcohols (ribitol, sorbitol, and erythritol) produced by several algal cells of the class Eucoccus of Chlorophyta phylum can be absorbed by fungi (A.…”
Section: Introductionmentioning
confidence: 99%
“…The organic matter produced by algae through photosynthesis is utilized by fungi, while algae bene t from the winding and protection of fungal laments, absorbing various nutrients needed for growth from the environment (Jiang et al 2019). Studies have shown that in the process of symbiosis between microalgae and fungi, the sugar alcohols (ribitol, sorbitol, and erythritol) produced by several algal cells of the class Eucoccus of Chlorophyta phylum can be absorbed by fungi (A.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, algae-bacteria/fungal symbiont technology has received widespread attention in the research and application of wastewater treatment because of its advantages of good effect and low cost. The organic matter produced by algae through photosynthesis was utilized by fungi, while algae benefited from the winding and protection of fungal filaments, absorbing various nutrients needed for growth from the environment (Jiang et al, 2019;Satpati et al, 2023). Studies had shown that in the process of symbionts between microalgae and fungi, the sugar alcohols (ribitol, sorbitol, and erythritol) produced by several algal cells of the class Eucoccus of Chlorophyta phylum can be absorbed by fungi (Mukhin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many breakthrough achievements had been achieved in the research of algae treatment technology for biogas purification and slurry (Cao et al, 2017;Jiang et al, 2019;Wrede et al, 2014). However, technical bottlenecks in difficult extraction and low purification efficiency of single microalgae have prevented this technique from being widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the biomass and lipid accumulation were also greatly enhanced (Wrede et al, 2014). Jiang et al (2019) reported that the algae-fungi symbiotic system of Chlorella variabilis and Ganoderma lucidum exhibited good efficiencies for COD, TN, TP, and ammonia nitrogen (NH 3 -N) reduction. Zhou et al (2012) optimized the fungi pelletization-assisted bioflocculation technology for efficient microalgae harvesting and the separated by filtration fungi--algae pellets were reused as immobilized cells for treatment of centrate and diluted swine manure wastewater.…”
Section: Introductionmentioning
confidence: 99%